Influence of a novel scaffold composed of polyurethane, hydroxyapatite, and decellularized bone particles on the healing of fourth metacarpal defects in mares. Issue 5 (5th May 2021) - Grzeskowiak, Remigiusz M.; Alghazali, Karrer M.; Hecht, Silke; Donnell, Robert L.; Doherty, Thomas J.; Smith, Christopher K.; Anderson, David E.; Biris, Alexandru S.; Adair, Henry S.
Abstract: Objective: To determine the effect of a novel scaffold, designed for use in bone regeneration, on healing of splint bone segmental defects in mares. Study design: In vivo experimental study. Sample population: Five adult mares (4–10 years old; mean weight, 437.7 kg ± 29 kg). Methods: Bilateral 2‐cm full‐thickness defects were created in the fourth metacarpal bones (MCIV) of each horse. Each defect was randomly assigned to either a novel scaffold treatment (n = 5) or an untreated control (n = 5). The scaffold was composed of polyurethane, hydroxyapatite, and decellularized bone particles. Bone healing was assessed for a period of 60 days by thermography, ultrasonography, radiography, and computed tomography (CT). Biopsies of each defect were performed 60 days after surgery for histological evaluation. Results: On the basis of radiographic analysis, scaffold‐treated defects had greater filling (67.42% ± 26.7%) compared with untreated defects (35.88% ± 32.7%; P = .006). After 60 days, CT revealed that the density of the defects treated with the scaffolds (807.80 ± 129.6 Hounsfield units [HU]) was greater than density of the untreated defects (464.80 ± 81.3 HU; P = .004). Evaluation of histology slides provided evidence of bone formation within an average of 9.43% ± 3.7% of the cross‐sectional area of scaffolds in contrast to unfilled defects in which connective tissue was predominant throughout the biopsy specimens. Conclusion: The novel scaffold was biocompatible and supported bone formation within the MCIV segmental defects. Clinical significance: This novel scaffold offers an effective option for filling bone voids in horses when support of bone healing is indicated.